ANALISIS FAKTOR YANG MEMPENGARUHI FIRM VALUE PADA PERUSAHAAN MANUFAKTUR TAHUN 2017-2019 - Eistevania Aswie; Elizabeth Sugiarto Dermawan (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
The purpose of this research is to determine the extent of the influence of dividend policy, profitability, leverage, institutional ownership and firm size on firm value ofmanufacturing companies listed on the Indonesia Stock Exchange (BEI) for the period of 2017-2019. Purposive sampling method is used in this method with total data 50 companies and 150 samples. This study using multiple regression analysis which isprocessed with SPSS 22 program and Microsoft Excel 2019. The results of this studyindicate that profitability and firm size have a significant positive effect on firm value. However, dividend policy, leverage, and institutional ownership has no significant effect on firm value. The implication of this study is the need to increase firm’s profitability and size to increasefirm’s value which will attract investor’s interest to invest.